2022
DOI: 10.3390/met12050847
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of High-Entropy Nitride Coatings

Abstract: The interest in nitride coatings based on high-entropy alloys (HEAs) has increased rapidly in the last decade. According to a number of papers, such high-entropy nitride (HEN) coatings have a single-phase structure and properties that significantly exceed those of simpler nitride systems. These properties include high hardness, wear resistance, oxidation resistance and thermal stability. It is believed that these distinctive properties are due to the high entropy of mixing, which increases with an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 187 publications
2
10
0
Order By: Relevance
“…The voids/pores can provide an initiation site for further damage and contribute to a higher erosion rate [39,40]. In comparison to some of the studies on HEN coatings discussed above, the (AlCrTiMoV)N coatings investigated in this study showed comparable results [8][9][10][11][12][13][14][15][16][17]. Th B1 FCC structure is consistent with the findings presented in this study.…”
Section: Wear and Erosion Resistancesupporting
confidence: 88%
See 2 more Smart Citations
“…The voids/pores can provide an initiation site for further damage and contribute to a higher erosion rate [39,40]. In comparison to some of the studies on HEN coatings discussed above, the (AlCrTiMoV)N coatings investigated in this study showed comparable results [8][9][10][11][12][13][14][15][16][17]. Th B1 FCC structure is consistent with the findings presented in this study.…”
Section: Wear and Erosion Resistancesupporting
confidence: 88%
“…The coating contains spherical metallic droplets, which lower the bulk hardness and are believed to detrimentally influence the coating perfor mance. The wear rate of (AlCrTiMoV)N was measured to be 1.35 × 10 −15 m 3 /(m*N), in othe words half the wear rate of the TiN coating, showing a better wear resistance than TiN Sand particle erosion tests showed an increase in the erosion rate with increasing impinge ment angles: erosion rates of 26 μg/g at 30° to 62 μg/g at 90°, higher than that measured In comparison to some of the studies on HEN coatings discussed above, the (AlCr-TiMoV)N coatings investigated in this study showed comparable results [8][9][10][11][12][13][14][15][16][17]. The B1 FCC structure is consistent with the findings presented in this study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, the increase in the microhardness of the films can be associated with the minimum number of dislocation sources in the grains and the predominant effect of the grain-boundary deformation mechanism through the determining role of grain boundaries. The inclusions of the nitrogen-containing phases are mainly concentrated at the grain boundaries, which themselves have a high microhardness [ 38 ]. An additional factor may be internal compressive stresses associated with a feature of plasma treatment: a high velocity of the oxidation front from the surface to the depth of the coating.…”
Section: Resultsmentioning
confidence: 99%
“…However, the stability of nitrides against oxidation, especially under OER conditions, has to be taken into consideration. [28][29][30] Thin-film materials libraries [31] in the form of continuous composition spreads were fabricated by reactive cosputter deposition on 4-inch-diameter thermally oxidized Si substrates. Using materials libraries is advantageous: in one step many different compositions are fabricated and their properties can be screened using so-called high-throughput characterization methods.…”
Section: Introductionmentioning
confidence: 99%